2013
DOI: 10.1186/1471-244x-13-61
|View full text |Cite
|
Sign up to set email alerts
|

Web-based guided self-help for employees with depressive symptoms (Happy@Work): design of a randomized controlled trial

Abstract: BackgroundDepressive disorders are highly prevalent in the working population and are associated with excessive costs for both society and companies. Effective treatment for employees with depressive symptoms in occupational health care is limited. The purpose of this study is to investigate the effectiveness and cost-effectiveness of an indicated preventive web-based guided self-help course for employees with depressive symptoms.MethodsThe study is a two-arm randomized controlled trial comparing a web-based g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…The design and short-term outcomes of this study have been described in detail elsewhere [ 40 , 41 ]. Therefore, we will describe the design briefly.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The design and short-term outcomes of this study have been described in detail elsewhere [ 40 , 41 ]. Therefore, we will describe the design briefly.…”
Section: Methodsmentioning
confidence: 99%
“…The design of this study has been published elsewhere [40]. A process evaluation of this study (submitted paper) revealed that the intervention was conducted according to protocol and seemed feasible for further implementation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was a randomized controlled trial with 2 arms: a Web-based guided self-help course called Happy@Work and a CAU group. The full design of the study has been described in detail elsewhere [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Data on cost-effectiveness has not been presented in any of the afore-mentioned studies on web-based stress-management for employees. For web-based interventions, studies currently investigate the cost-effectiveness of mental health interventions for workers, including studies of a workers’ health surveillance mental module [29] and a guided self-help course for workers with depressive symptoms [30]. However, to the best of our knowledge, there are no studies with full economic evaluations of the cost-effectiveness of web-based stress-management training for employees.…”
Section: Introductionmentioning
confidence: 99%